2015
DOI: 10.1590/s1677-5538.ibju.2015.01.15
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor (IgF)-I, IgF binding protein-3, and prostate cancer: correlation with gleason score

Abstract: Introduction Non-androgenic growth factors are involved in the growth regulation of prostate cancer (PCa).Objective This is the first Brazilian study to correlate, in a population of patients operated for PCa, PSA, total testosterone, insulin-like growth factor-I (IGF-I) and insulin-like growth factor-binding protein-3 (IGFBP-3) with Gleason score and to compare with a control group with benign prostate hyperplasia (BPH).Materials and Methods This retrospective single-center study included 49 men with previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
1
6
0
1
Order By: Relevance
“…Previous clinical studies investigated the association between serum IGF‐1 levels and tumor aggressiveness, but their results were not consistent with the epidemiologic data28, 29, 30 due to small sample size, such that they had insufficient statistical power to discriminate tumor grade. All three of the quoted studies demonstrated trends toward lower IGF‐1 level in high‐grade disease, but these fell short of statistical significance 28, 29, 30.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Previous clinical studies investigated the association between serum IGF‐1 levels and tumor aggressiveness, but their results were not consistent with the epidemiologic data28, 29, 30 due to small sample size, such that they had insufficient statistical power to discriminate tumor grade. All three of the quoted studies demonstrated trends toward lower IGF‐1 level in high‐grade disease, but these fell short of statistical significance 28, 29, 30.…”
Section: Discussionmentioning
confidence: 92%
“…All three of the quoted studies demonstrated trends toward lower IGF‐1 level in high‐grade disease, but these fell short of statistical significance 28, 29, 30. Of these previous studies, the one with the largest sample size ( n  =   242) used a GS based on prostatic biopsy, rather than surgical pathology 30.…”
Section: Discussionmentioning
confidence: 96%
“…The inverse correlation between PSA and IGFBP-3 could make IGFBP-3 a possible biochemical marker of disease control in prostate cancer patients. (25) The present study has limitations such as not performing measurements on IGFBP-3 and not doing more clinical examinations, such as a digital rectalexaminations for confirmation of any abnormality in the prostate of subjects with PSA levels above 4 ng/L.…”
Section: Discussionmentioning
confidence: 92%
“…On the other hand, metformin treatment in HFD-fed mice was associated with decreased expression of GHR and IGFBP3. Interestingly, GHR appeared to be upregulated in colorectal and breast cancer samples (48), and its downregulation is associated with better metabolic profile and lower cancer incidence (49), whereas IGFBP3 levels are elevated in patients with prostate cancer (50), suggesting that metformin could be partially exerting its beneficial effects under HFD conditions through the regulation of the local expression of different GH/IGF1 axis components. Remarkably, whether these expression changes are accompanied by alterations in protein levels is still to be defined.…”
Section: Discussionmentioning
confidence: 99%